1993
DOI: 10.1073/pnas.90.11.4986
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Ca2+ pool content is linked to control of cell growth.

Abstract: A close correlation was observed between intracellular Ca2+ pool depletion and refiling and the onset of DNA synthesis and proliferation of DDT,MF-2 smooth muscle cells. The intracellular Ca2+ pump inhibitors 2,5-di-tert-butylhydroquinone (DBHQ) and thapsigargin (TG) specificafly emptied identical inositol 1,4,5-trisphosphate (InsP3)-sensitive Ca2+ pools and both arrested cell growth at concentrations corresponding to Ca2+ pump blockade. However, an important distinction was observed between the two inhibitors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
180
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 246 publications
(189 citation statements)
references
References 18 publications
9
180
0
Order By: Relevance
“…If the cell is not capable of maintaining an adequate level of Ca 2+ in intracellular stores, many cellular functions including posttranslational modifications of recombinant proteins will be abnormal. Store depletion may elicit problematic protein trafficking, sarcoplasmic reticulum (SR) stress (Cudna and Dickson 2003), growth arrest (Short et al 1993), and apoptosis (He et al 1997) caused by the resulting disturbance of posttranslational protein modification. Ca 2+ influx through SOCE involves keeping a sustained high Ca 2+ concentration in the Ca 2+ stores and refilling the SR when it releases Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…If the cell is not capable of maintaining an adequate level of Ca 2+ in intracellular stores, many cellular functions including posttranslational modifications of recombinant proteins will be abnormal. Store depletion may elicit problematic protein trafficking, sarcoplasmic reticulum (SR) stress (Cudna and Dickson 2003), growth arrest (Short et al 1993), and apoptosis (He et al 1997) caused by the resulting disturbance of posttranslational protein modification. Ca 2+ influx through SOCE involves keeping a sustained high Ca 2+ concentration in the Ca 2+ stores and refilling the SR when it releases Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, when thapsigargin was added to actively proliferating cells 24 h after growth stimulation, the growth inhibitory effect of thapsigargin was substantially reduced [8]. These findings led the authors to the conclusion that a specific cell cycle event necessary for the G0/G1 transition depends upon signals generated from functional InsP3-sensitive Ca 2÷ stores [9,10]. However, a question *Corresponding author.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 90%
“…The increase in [Ca2÷]i is postulated to serve as a mitogenic signalling for re-entry into the cell cycle at the G0/G1 border [6,7]. Recently, Gill and his colleagues [8][9][10] have demonstrated that thapsigargin, which is a selective inhibitor ofendoplasmic reticulum Ca 2+ pump [11] and depletes InsP3-sensitive Ca 2+ stores [12,13], potently inhibits cell proliferation. In their experiments, density-arrested DDT1MF-2 smooth muscle cells were growth-stimulated by trypsinizing and replating into fresh growth media.…”
Section: Introduction 2 Materials and Methodsmentioning
confidence: 99%
“…A major function of the ER is to sequester and release calcium for use in intracellular signaling (Carafoli, 1987). Moreover, the ER calcium pool is essential for a number of vital cellular functions which include protein processing (Lodish, 1992;Gething, 1992), maintaining high translation rates of newly transcribed messages , preserving the structural integrity of the ER (Koch et al, 1988;Booth and Koch, 1989), and regulating cell proliferation and cell cycle progression (Short et al, 1993). In a previous report, we showed that viral protein-mediated induction of GRP78 synthesis is accompanied by decreased calcium efflux out of the ER lumen following inhibition of ER-associated calciumATPase activity by thapsigargin .…”
Section: Discussionmentioning
confidence: 99%